ANALISA ALOKASI ANGGARAN KEMENTERIAN PERTANIAN TAHUN 2015 – 2017 - Irianto, Mochamad Fariz; Syamsiyah, Nur; Vio, Adistya (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The ability of the nation to fulfill food needs from domestic production, manage food policy independently, and protect and prosper the farmers as the main actors of food agriculture will realize domestic food sovereignty. Thus, it is necessary to support large enough funds to implement it. However, the allocation of funds (APBN) for the Ministry of Agriculture annually is always at a very low position. Therefore, the purpose of this study is to analyze the budget allocation of the Ministry of Agriculture 2015-2017 on the priority scale of the Ministry's budget Agriculture in the year. This research is descriptive research with qualitative method. The results of this study indicate that from the budget allocation given to the Ministry of Agriculture during 2015-2017 and the achievements of the Ministry of Agriculture indicator in that year, many achievements of the strategic objectives that obtained the category successfully and very successful. Even if there is one achievement that has less successful category, that is production of soybean in 2016-2017. Thus, from the allocation of funds devoted to the Ministry of Agriculture can achieve its strategic objectives well. However, it remains a record for the Ministry of Agriculture to maximize its work in improving its strategic objectives next year, especially in soybean production.